Risk factors towards Public-Private Partnerships (PPP) projects implementing building information modelling (BIM) in the United Kingdom (UK): a lesson learnt for Malaysia - Abdullah Habib, Siti Nora Haryati; Ismail, Syuhaida; Syed Khuzzan Alhabshi, Sh Mazlina (Malaysian Institute of Planners, 2020)
Public Private Partnership (PPP) projects involve stakeholders engaged in various contract structures in a lengthy contract duration. Such situations expose the projects to risks related to collaborative working and information integration. Building Information Modelling (BIM) is seen as a mechanism to improve the collaboration and integration in the PPP projects. However, BIM also exposes its users to additional risk when the barriers in sharing information are reduced. Therefore, the aim of this paper is to investigate the BIM risk factors that have significant impact towards PPP projects implementing BIM. Since the United Kingdom (UK) is considered advanced in practising PPP and BIM, this study investigates the UK industry players’ views on what they considered as significant BIM factors in PPP projects. Consequently, the study has identified six (6) most significant BIM risk factors through questionnaire and experts’ interviews. The findings provide a lesson learnt for Malaysia to consider the BIM risks in implementing BIM in PPP projects.